2013
DOI: 10.1007/978-3-642-39649-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fast Landscape Changes: The Case of Solar Modules on Agricultural Land

Abstract: Abstract. Fast land changes may lead to new unadaptive structures and functions and may remain unnoticed causing national as well as local land survey agencies to be ineffective. This argument will be displayed by means of a real case in central Italy and by focusing on the booming sprawl of photovoltaic solar modules on arable land. In Marche Region such a change has come about with an exponential pace in terms of area coverage. The figure emerging from our experimental survey shows 800 ha of arable lands sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Finally, an agrivoltaic solution can also be offered as a solution to the resentment against conversion of arable farmlands into PV farms due to policies which favor PV farms causing a reduction in food production [46].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an agrivoltaic solution can also be offered as a solution to the resentment against conversion of arable farmlands into PV farms due to policies which favor PV farms causing a reduction in food production [46].…”
Section: Introductionmentioning
confidence: 99%
“…Such a change took place with an exponential pace in term of surface. A recent work [48] showed that, in a single region (Marche) in central Italy, 12,000 new facilities were installed in less than five years for a total power of more than 784,000 kW, spoiling 600 ha of arable lands. Many of the installations were not initiated by farmers seeking to broaden their business or to penetrate the renewables market, but by external companies seeking the rich flow of national subsidies, in constant search for farmers and landowners willing to sell parcels.…”
Section: Case 2: Solar Mirrors Encroaching Arable Landmentioning
confidence: 99%
“…The growing land footprint of solar PV presents social and spatial challenges, which are exacerbating the competition for land between agriculture versus energy production [5,[23][24][25]. The U.S. Department of Energy Sunshot Vision Study forecasts that solar energy capacity will be nearly 329GW by 2030, which will necessitate approximately 1.8 million acres of land for ground-mounted systems [26].…”
Section: Introductionmentioning
confidence: 99%